Study on the Development and Influencing Factors of Psychological Empowerment - Yang, Shuai; Eunjoo Oh (International Journal of Social Sciences and Public Administration, 2024)
Psychological empowerment, as a core concept in contemporary management, has garnered significant attention in recent years within the fields of organizational behavior and human resource management. By enhancing employees’ autonomy, competence, meaning, and impact, psychological empowerment effectively stimulates intrinsic motivation, thereby improving job satisfaction and organizational effectiveness. This study aims to systematically review the evolution of the concept of psychological empowerment, including its dimensions and measurement methods. It examines key antecedents affecting psychological empowerment, such as individual characteristics (e.g., personality traits, self-efficacy), job characteristics (e.g., task variety, job significance), and organizational features (e.g., organizational climate, empowerment culture), as well as outcomes like job satisfaction, job performance, and organizational commitment. Based on these findings, potential future research directions are proposed, providing valuable insights for the further development and practical application of psychological empowerment theory.